The (Un)Making of the class in the MST: Dilemmas of the Anti-Systemic Struggle - Machado, Eliel (Pontifícia Universidade Católica de São Paulo, 2007)
This article discusses, as the title suggests, the limits and the potential of the struggle carried out by the MST against neoliberal capitalism that was implemented in the 1990s, which in a certain way has placed the MST in front of a politically and ideologically difficult dilemma: to grab the means of production while at the same time struggling for socialism.